2018
DOI: 10.3389/fphys.2018.00028
|View full text |Cite
|
Sign up to set email alerts
|

Select Skeletal Muscle mRNAs Related to Exercise Adaptation Are Minimally Affected by Different Pre-exercise Meals that Differ in Macronutrient Profile

Abstract: Background: Substantial research has been done on the impact of carbohydrate and fat availability on endurance exercise adaptation, though its role in the acute adaptive response to resistance exercise has yet to be fully characterized.Purpose: We aimed to assess the effects of a pre-resistance exercise isocaloric mixed meal containing different amounts of carbohydrates and fat, on post-resistance exercise gene expression associated with muscle adaptation.Methods: Thirteen young (age 21.2 ± 1.6 year), recreati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…These genes were therefore analyzed at 0.5, 3, and 24 h post-loading in bioengineered mouse muscle to enable a direct comparison with humans after acute RE. First, the majority of these genes predominantly increased at 3 h post-loading and returned to basal levels at 24 h. This temporal gene regulatory profile has been observed several times in response to exercise in vivo in which gene expression tends to peak at 3-8 h post-exercise (Barrès et al, 2012;Chen et al, 2002;Drummond et al, 2008;Knuiman et al, 2018;Kuang et al, 2020) and generally returns to basal levels within 24 h Liu et al, 2010;Yang et al, 2005).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…These genes were therefore analyzed at 0.5, 3, and 24 h post-loading in bioengineered mouse muscle to enable a direct comparison with humans after acute RE. First, the majority of these genes predominantly increased at 3 h post-loading and returned to basal levels at 24 h. This temporal gene regulatory profile has been observed several times in response to exercise in vivo in which gene expression tends to peak at 3-8 h post-exercise (Barrès et al, 2012;Chen et al, 2002;Drummond et al, 2008;Knuiman et al, 2018;Kuang et al, 2020) and generally returns to basal levels within 24 h Liu et al, 2010;Yang et al, 2005).…”
Section: Discussionmentioning
confidence: 87%
“…It is also worth noting that analysis of human muscle involved pooling transcriptomic datasets across 110 biopsies (37 pre/57 post after outlier removal) over multiple studies (Turner et al, 2019b ), and therefore encompassed all timepoints from immediately post and up to 24 h post‐acute RE. Where, gene expression is typically greatest at 3–8 h post exercise (Barrès et al, 2012 ; Chen et al, 2002 ; Drummond et al, 2008 ; Knuiman et al, 2018 ; Kuang et al, 2020 ) and generally returns to basal levels within 24 h (Egan & Zierath, 2012 ; Liu et al, 2010 ; Yang et al, 2005 ). Therefore, the majority of transcriptional alterations detected at 3 h in the bioengineered muscle may also be exemplifying this temporal activation in gene expression post‐loading.…”
Section: Resultsmentioning
confidence: 99%
“…Cytoskeletal remodeling is a common feature of eukaryotic cells exposed to real and simulated microgravity, including endothelial cells ( Cotrupi et al, 2005 ; Versari et al, 2013 ; Barravecchia et al, 2018 ). In HUVEC grown in the RWV, we have shown that cytoskeletal disorganization plays a role in triggering mitophagy ( Locatelli et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this paper, we investigated the role of cytoskeletal disorganization in orchestrating endothelial response to simulated microgravity. Because of the heterogeneity of the endothelium, we used two different types of EC, i.e., human endothelial cells from umbilical vein (HUVEC) and human dermal microvascular endothelial cells (HDMEC), a model of macro- and microvascular EC, respectively, which have been used for studies in real and simulated microgravity ( Shi et al, 2012 ; Grenon et al, 2013 ; Versari et al, 2013 ; Barravecchia et al, 2018 ; Cazzaniga et al, 2019 ; Locatelli et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…These effectors include the activators of pyruvate dehydrogenase kinase 4 (PDK4), forkhead box O1 (FoxO1), ERRα, and PPARs gene expression. And enhanced PDK4 can phosphorylate PDH to inactivate it and prevent pyruvate from entering TCA, converting cells from glucose metabolism to lipid metabolism and then meet the energy needs of exercise (Knuiman et al, 2018 ). In addition, as a downstream factor activated by the SIRT1-PGC-1α axis, TFAM can play a role in diseases such as diabetes and diabetic peripheral neuropathy by enhancing the function of mitochondria, promote the complete oxidation of fatty acids in mitochondria, and provide a large number of sources of ATP for cells (Chandrasekaran et al, 2019 ).…”
Section: The Expression and Activity Of Sirt1 Are Regulated By Many Dimensionsmentioning
confidence: 99%